# How do you simplify #(-7i)(-3i)(-5-i)#?

##### 2 Answers

Sep 27, 2016

#### Explanation:

first multiply two of the terms*

you now have

now multiply that with

you get

*you can chose any two but these are easier

Sep 27, 2016

#### Explanation:

Begin by multiplying the 2 leading terms.

#(-7i)(-3i)=21i^2=-21#

#color(orange)"Reminder " color(red)(bar(ul(|color(white)(a/a)color(black)(i^2=(sqrt(-1))^2=-1)color(white)(a/a)|)))# The original question can now be expressed as.

#-21(-5-i)=105+21i#